HUBUNGAN MANAJEMEN WAKTU BELAJAR TERHADAP HASIL BELAJAR SISWA XI PAKET C DI SPNF SKB KOTA PALEMBANG - Aulia Fadsyah, Nazwa; Helmi, Henny; Shomedran, Shomedran; Saputra, Ardi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the relationship between study time management and learning outcomes of class XI students in the Package C program at SPNF SKB Palembang City. This study uses a quantitative correlational approach. The population and sample of the study amounted to 50 class XI Package C students. Data collection techniques used questionnaires and documentation. Data analysis techniques used descriptive statistics and Pearson Product Moment correlation tests. The results showed that study time management was in the high category, while learning outcomes were in the good category. The results of the correlation test showed a significant positive relationship with a moderate level (r = 0.403; p < 0.05). This indicates that the better the study time management, the better the student learning outcomes, although it is not the only influencing factor.